Ultrasound‐assisted synthesis of benzoxazine monomers: thermal and mechanical properties of polybenzoxazines. Issue 1 (28th August 2012) - Vengatesan, Muthukumaraswamy Rangaraj; Devaraju, Subramani; Kannaiyan, Dinakaran; Song, Jang Kun; Alagar, Muthukaruppan
Abstract A series of benzoxazine monomers (P‐aea2–P‐aea8) were prepared from appropriate aromatic diamines containing linear aliphatic ether chains with phenol and formaldehyde through the Mannich reaction under ultrasonication and conventional methods. Based on the reaction performance, the ultrasonication method has been found to be more facile and convenient for the synthesis of benzoxazine monomer than the conventional method. The synthesized monomers undergo curing at a lower temperature than that of conventional benzoxazine (Ba‐A) monomer as evidenced from differential scanning calorimetric analysis. The presence of an aliphatic ether core in the benzoxazine monomer aids in lowering the curing temperature, which seems to vary linearly with chain length. Thermally polymerized benzoxazine (poly(P‐aeas)) shows an enhanced tensile and flexural strength. Copyright © 2012 Society of Chemical Industry